Financial Behavior and Financial Satisfaction of Non-Teaching Personnel in a City Schools Division in Negros Occidental - Bargaso, Ma. Venice June; Padilla, Nenette; Bual, Joel (Technium Social Sciences Journal, 2024)
Financial behavior and financial satisfaction are two essential elements in the lives of the human being like non-teaching personnel. Hence, this study assessed the financial behavior of non-teaching personnel in a city schools division in Negros Occidental in terms of spending habits, borrowing practices, repayment practices, savings, and investments relative to age, sex, civil status, position level, and net take-home pay. Likewise, it determined their financial satisfaction in terms of financial solvency and financial knowledge relative to the demographics. Also, it compared their financial behavior and financial satisfaction when grouped according to the demographics. Lastly, it correlated their financial behavior and financial satisfaction. The study utilized the descriptive-comparative and correlational research design. It was responded by 106 non-teaching personnel and was determined using stratified random sampling. The instruments used were adopted-modified questionnaires. In analyzing the data, mean, standard deviation, Mann Whitney U test, and Spearman rank correlation were employed. Meanwhile, the researcher adhered to the guidelines established by the Philippine Health Research Ethics Board (PHREB). Generally, they have a very high financial behavior and high financial satisfaction. In comparing their financial behavior when grouped according to the demographics, only the net take-home pay has the significant difference. In terms of the financial satisfaction, all demographics resulted no significant differences. Regarding the relationship between the two constructs, there was a significant relationship between their financial behavior and financial satisfaction. Hence, to improve their satisfaction financially, their behavior towards finances should be given attention.